(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
In response to unwise and inappropriate antimicrobial drug (AMD) use, antimicrobial drug resistance (AMDR) is rising globally. The present research was performed to find out and evaluate the perceptions, practices, and knowledge (PPK) of the farmers regarding AMD use and AMDR propagation in rural households. The study was conducted using a pre-tested questionnaire upon 200 respondents with a duration of 5 months in selected areas of Cumilla district, Bangladesh. The correlation analysis showed a significant (p<.01) relationship between farmers’ knowledge and practicing proper administration of drugs in the animal. The sex of the respondents was also found to be correlated with the understanding of Antibiotic Resistance (AR) (p<.01), AR transmission (p<.05), and propagation from livestock to humans (p<.01). Additionally, through the qualitative analysis, we found the powerful impacts of media availability and accessibility, participation in the training program, and good quality education on the improvement of farmers’ PPK. Therefore, the government must need to emphasize this topic and educate the farmers about AR to control the spread of AR in order to secure both animal and public health. Asian Australas. J. Biosci. Biotechnol. 2022, 7(2), 57-74